Enhancing the Photocatalytic Performance of BiOClxI1−x by Introducing Surface Disorders and Bi Nanoparticles as Cocatalyst. Issue 14 (23rd July 2015) - Huang, Yongchao; Long, Bei; Li, Haibo; Balogun, Muhammad‐Sadeeq; Rui, Zebao; Tong, Yexiang; Ji, Hongbing
<x xml:space="preserve">Abstract</x> Photocatalysis has emerged as a promising method for industrial sewage elimination. The main bottleneck of this process is the development of an efficient, stable, and cost‐effective catalyst that can oxidize pollution under visible light. Herein, surface disorders and Bi nanoparticles are successfully introduced into BiOClxI1−x nanosheets using low‐cost NaBH4 as a reductant in a liquid‐phase environment. Benefiting from the enhanced charge separation, transfer, and donor density resulting from the formation of surface disorders, and Bi deposition as cocatalyst, the photocatalytic performance of the reductive BiOClxI1−x nanosheets is fivefold higher than that of the untreated BiOClxI1−x nanosheets for phenol degradation under visible light irradiation. Additionally, the reductive BiOClxI1−x nanosheets have a superior stability after five cycles.